2010
DOI: 10.1111/j.1469-8137.2010.03356.x
|View full text |Cite
|
Sign up to set email alerts
|

Flotation preferentially selects saccate pollen during conifer pollination

Abstract: Summary• Among many species of living conifers the presence of pollen with air bladders (saccate pollen) is strongly associated with downward-facing ovules and the production of pollination drops. This combination of features enables saccate pollen grains captured in the pollination drop to float upwards into the ovule. Despite the importance of this mechanism in understanding reproduction in living conifers and in extinct seed plants with similar morphologies, experiments designed to test its effectiveness ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 37 publications
1
19
0
2
Order By: Relevance
“…This assumption comes from a thorough paternity study conducted on seeds, seedlings and juveniles of A. angustifolia (Bittencourt and Sebbenn, 2007). It contrasts with the fact that pollen grains in Araucariaceae are among the largest non-saccate (i.e., without inflated air bladders) grains of any conifer (Leslie, 2010), raising questions about the effectiveness of wind dispersal for these large, non-floating pollen grains (Sousa and Hattemer, 2003), and its role in long-range gene flow (Pye, 2005). Results indicating that pollen dispersal is more important than seed dispersal for long-distance gene flow were obtained from two small, highly fragmented and isolated patches of A. angustifolia (Bittencourt and Sebbenn, 2007), where seeddisperser parrots could be scarce or even absent.…”
Section: Future Research Avenuesmentioning
confidence: 99%
“…This assumption comes from a thorough paternity study conducted on seeds, seedlings and juveniles of A. angustifolia (Bittencourt and Sebbenn, 2007). It contrasts with the fact that pollen grains in Araucariaceae are among the largest non-saccate (i.e., without inflated air bladders) grains of any conifer (Leslie, 2010), raising questions about the effectiveness of wind dispersal for these large, non-floating pollen grains (Sousa and Hattemer, 2003), and its role in long-range gene flow (Pye, 2005). Results indicating that pollen dispersal is more important than seed dispersal for long-distance gene flow were obtained from two small, highly fragmented and isolated patches of A. angustifolia (Bittencourt and Sebbenn, 2007), where seeddisperser parrots could be scarce or even absent.…”
Section: Future Research Avenuesmentioning
confidence: 99%
“…Pine pollen must thus float on water in order to reach the nucellus. The buoyancy of marked live pollen during deposition and pollination can be tested directly and functionally by a range of methods (Matthews and Blalock 1981;Leslie 2010).…”
Section: Discussionmentioning
confidence: 99%
“…(2002) showed that saccate pollen is rapidly wetted and pulled inside the pollination drop rather than remaining on its surface. But the most definitive and statistically well‐supported confirmation of the flotation hypothesis is the series of ingenious experiments reported in this issue of New Phytologist by Andrew Leslie (pp. 273–279), which clear up contrary and equivocal results of earlier studies by showing that saccate pollen is more efficiently floated up the micropylar canal than nonsaccate pollen, both in vitro and in vivo .…”
mentioning
confidence: 90%